Progress in Brain Computer Interface: Challenges and Opportunities - Saha, Simanto; Mamun, Khondaker A.; Ahmed, Khawza; Mostafa, Raqibul; Naik, Ganesh R.; Darvishi, Sam; Khandoker, Ahsan H.; Baumert, Mathias (Frontiers in Systems Neuroscience, 2021)
Brain computer interfaces (BCI) provide a direct communication link between the brain and a computer or other external devices. They offer an extended degree of freedom either by strengthening or by substituting human peripheral working capacity and have potential applications in various fields such as rehabilitation, affective computing, robotics, gaming and neuroscience. Significant research efforts on a global scale have delivered common platforms for technology standardisation and help tackle highly complex and nonlinear brain dynamics and related feature extraction and classification challenges. Time-variant psycho-neurophysiological fluctuations and their impact on brain signals impose another challenge for BCI researchers to transform the technology from laboratory experiments to plug-and-play daily life. This review summarises state-of-the-art progress in the BCI field over the last decades and highlights critical challenges.